How Does Green Training Boost Employee Green Creativity? A Sequential Mediation Process Model - Wu, Jianfei; Chen, Dan; Bian, Zejuan; Shen, Tiantian; Zhang, Weinan; Cai, Wenjing (Frontiers in Psychology, 2021)
Despite accumulated evidence from previous studies that green creativity is highly emphasized in various industries, limited research has been conducted in the context of public sectors. Drawing on the dynamic componential model of creativity and innovation in organizations, this paper aims to propose and test the relationship between green training and employees’ green creativity through green values and green intrinsic motivation sequentially. Based on the data collected in Chinese public sectors (N = 464) at two different time points, the results indicate that green training is positively related to green creativity. Moreover, this relationship is mediated by green values and green intrinsic motivation sequentially. The results in our study advance the emergent literature on green human resource management in the public sectors for the practical applications of training and creativity in terms of green management.